Emergency Approaches to Neurosurgical Conditions - Agrawal, Abhishek; Britz, Gavin (Springer International Publishing : Imprint: Springer, 2015)
This comprehensive guide answers commonly asked questions about neurosurgical conditions related to brain and spinal cord. Emergency Approaches to Neurosurgical Conditions fills the gap which arises after a diagnosis is made on the loved one, explaining the basics of neurosurgical diseases and their management. Emergency Approaches to Neurosurgical Conditions concentrates on the brain and spine, both in surgery and radiotherapy, as well as congenital and accident-related conditions. This comprehensive book which is part of a book-set including Comprehensive Guide to Neurosurgical Conditions, informs the reader on various symptoms to look for, and helps with the management of brain and spine surgery in chapters written by reputed neurosurgeons to help the physicians, the patients and their families.